Survival After Percutaneous Endoscopic Gastrostomy in Older Adults With Neurologic Disorders. (18th May 2016) - Kara, Ozgur; Kizilarslanoglu, Muhammet Cemal; Canbaz, Busra; Arik, Gunes; Varan, Hacer Dogan; Kuyumcu, Mehmet Emin; Kilic, Mustafa Kemal; Sumer, Fatih; Yesil, Yusuf; Yavuz, Burcu Balam; Cankurtaran, Mustafa; Ozturk, Omer; et al.
Abstract : Background : Percutaneous endoscopic gastrostomy (PEG) tube placement is a common procedure performed to provide a route for enteral feeding. We aimed to examine the survival after PEG in older adults with neurologic disease and to demonstrate the factors associated with mortality. Methods : We analyzed the data of 500 patients who underwent PEG placement between 2005 and 2015 at a university hospital. The data included age, sex, follow‐up duration, comorbidities, medications, indications for PEG, complications, and laboratory results. Related risk factors and mortality rates were analyzed. Results : Median age was 77 years. Median survival time after PEG placement was 13.9 months. The 30‐day, 3‐month, 1‐year, 2‐year, 3‐year, and 5‐year mortality rates were 11.3%, 28.3%, 46.8%, 56.3 %, 63.0%, and 67.8%, respectively. Stroke was independently correlated with mortality (odds ratio [OR], 2.20; 95% confidence interval [CI], 1.52–3.19; P < .001). Overall survival time after PEG placement was shorter in patients with stroke than without stroke (11.4 vs 27.1 months, P = .014). In multivariate logistic regression analyses, preprocedural neutrophil percentage (OR, 1.10; 95% CI, 1.02–1.17, P = .015) and late complications (OR, 9.2; 95% CI, 1.80–46.90; P = .008) were independent risk factors for mortality in the stroke subgroup. Prophylactic antibiotic usage (OR, 0.07; 95% CI, 0.17–0.29; P < .001) and hyperlipidemia (OR, 0.30; 95% CI, 0.86–1.00; P = .048) were independently and inversely correlated with mortality in stroke patients. Conclusions : Stroke patients had higher mortality rates than other neurological indications for PEG. In stroke patients with PEG, neutrophil percentage was independently correlated with mortality, while hyperlipidemia and preprocedural antibiotic usage were independently related with survival.